2018
DOI: 10.1590/s2175-97902018000100031
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of chemical preservatives on human fibroblast cells

Abstract: Preservatives are widely used substances that are commonly added to various cosmetic and pharmaceutical products to prevent or inhibit microbial growth. In this study, we compared the in vitro cytotoxicity of different types of currently used preservatives, including methylparaben, imidazolidinyl urea (IMU), and sodium benzoate, using the human newborn fibroblast cell line CCD1072Sk. Of the tested preservatives, only IMU induced a reduction in cell viability, as shown using the MTT assay and propidium iodide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Among in vitro assays, cytotoxicity tests are simple, reproducible, inexpensive to perform, and suitable for evaluation of basic biologic properties [41]. These studies also provide a significant amount of information can be conducted under controlled conditions and may elucidate the mechanisms of cellular toxicity [41,54,55]. Several methods are available for cytotoxicity testing and among them, the MTT-based colorimetric assay is a standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Among in vitro assays, cytotoxicity tests are simple, reproducible, inexpensive to perform, and suitable for evaluation of basic biologic properties [41]. These studies also provide a significant amount of information can be conducted under controlled conditions and may elucidate the mechanisms of cellular toxicity [41,54,55]. Several methods are available for cytotoxicity testing and among them, the MTT-based colorimetric assay is a standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the proinflammatory cytokines from bone marrow stem cells, the use of adipose derived mesenchymal stem cells and fibroblasts provides a proresolving, anti-inflammatory set of cytokines and other molecules for use in skin care therapeutics . Seven, most cosmetic products will need preservative systems unless they are an anhydrous formulation, with those systems often being cytotoxic and irritating, potentially damaging the cells, including fibroblasts in the skin (Spindola et al, 2018). While preservatives are necessary for non-anhydrous formulations that are not packaged in sterile, single use containers, care must be used in the choice of the preservative to be used.…”
Section: Examples Of Potentially Harmful Chemicals In Skin Care Productsmentioning
confidence: 99%
“…In the case of cosmetic products, considering the specific route of topical application, the in vitro cytotoxicity testing on skin cell lines (in particular keratinocytes and fibroblasts) can be used for primary toxicological evaluation of new ingredients such as surfactants, colorants, preservatives, and additives. 2,[23][24][25] In this study, the human keratinocyte (HaCaT cell line) was used for evaluation of the Monascus pigments skin toxicity by using in vitro MTT assay. The results of the cytotoxicity of Monascus pigments against normal human keratinocytes were shown in Table 2 which indicated that Monascus pigments are nontoxic toward the normal skin cell in the in vitro study.…”
Section: Human Erythrocytes Cytotoxicity Assaymentioning
confidence: 99%